Overall drug treatment of idiopathic pulmonary fibrosis patients from national registries - a real-world study from Finland - Kaunisto Jaana; Salomaa Eija-Riitta; Koivisto Mari; Myllärniemi Marjukka (BMC, 2025)
Background Currently, two disease-modifying antifibrotic drugs are indicated for the treatment of idiopathic pulmonary fibrosis. The objective of this study was to analyse antifibrotic and overall prescription medication use of IPF patients in the real world.
Methods Data was collected from the FinnishIPF registry and the Registry of the Social Insurance Institution of Finland (SII). Purchases of all prescription medicines were assessed. The frequency, the initiation interval, the duration, and the breaks of the antifibrotic treatments were defined. The association between the prescription of antifibrotic therapy and different patient-related clinical parameters was studied. Accordingly, the relationships between the delay in starting therapy and patient-related variables were analysed.
Results Of the 263 IPF patients, 132 (50.2%) had started antifibrotic treatment during the study period 2011-2018. The mean interval from the diagnosis to the first purchase was 367 (SD 429) days. The antifibrotic drug was switched in 14% of patients. Discontinuation of therapy occurred most commonly during the first year of the treatment. The one-year persistence was 77.1% for pirfenidone and 78.9% for nintedanib. A tendency of treating patients under 75 years was noticed. Low forced vital capacity predicted earlier initiation of medication.
Conclusions The initiation of antifibrotics after diagnosis was slow, probably due to reimbursement limitations. Younger age at diagnosis affected treatment initiation although it is unknown which patients benefit most from these medications. The reasons for discontinuation of the antifibrotic therapy during the first year should be a focus in clinical work and further studies.